2021
DOI: 10.1039/d1cp02115j
|View full text |Cite
|
Sign up to set email alerts
|

Simple models for the quick estimation of ground state hydrogen tunneling splittings in alcohols and other compounds

Abstract: Models for the quick estimation of energy splittings caused by coherent tunneling of hydrogen atoms are evaluated with available experimental data for alcohols and improvements are proposed. The discussed models...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 129 publications
0
17
0
Order By: Relevance
“…Observed spectral splittings could be translated into torsional splittings, determined for the main isotopolog of α-fenchol as 16(1) cm −1 and 9(1) cm −1 in the OH stretch ground and excited state, respectively. As the tunneling interaction largely contributes to these splittings, they are characteristically [85] reduced to 7(3) and 3(1) cm −1 upon increasing the tunneling mass by hydroxy deuteration. Despite being calculated to be less delocalized, the deuterated alcohol shows a more even distribution of Raman activity across the split bands.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Observed spectral splittings could be translated into torsional splittings, determined for the main isotopolog of α-fenchol as 16(1) cm −1 and 9(1) cm −1 in the OH stretch ground and excited state, respectively. As the tunneling interaction largely contributes to these splittings, they are characteristically [85] reduced to 7(3) and 3(1) cm −1 upon increasing the tunneling mass by hydroxy deuteration. Despite being calculated to be less delocalized, the deuterated alcohol shows a more even distribution of Raman activity across the split bands.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, it has been shown that experimental tunneling splittings of protiated and deuterated alcohols (and also other series of compounds with hydrogen tunneling) can be directly correlated with each other as well, taking advantage of similar changes of the moment of inertia and the torsional wavenumber upon deuteration [85]. If the contributions to the assigned torsional splittings of α-fenchol are dominated by tunneling, and less by asymmetry, the isotope effect should be roughly captured by this model as well.…”
Section: Consistency Checks For Isotope Effectsmentioning
confidence: 91%
See 3 more Smart Citations